Redefining Education in The Millennial Age: The Role of Junior High Schools Khadijah Surabaya as A Center for Aswaja Smart Schools - Mahbubi, M; Ahmad, Amala Bilqis (STKIP Pesisir Selatan, 2025)
This study explores the role of SMP Khadijah Surabaya in shaping the educational landscape of the millennial generation through its ASWAJA Smart School model. With the rapid advancement of technology, the integration of Islamic values with modern educational tools has become a significant challenge for Islamic schools. SMP Khadijah Surabaya presents a unique approach by combining the traditional principles of Ahlussunnah Wal Jama'ah (ASWAJA) with smart school technologies to create an innovative learning environment. This research aims to investigate how this integration impacts students’ religious values, academic performance, and technological proficiency.Using a mixed-methods approach, the study combines qualitative data from interviews with teachers, administrators, and students, alongside quantitative analysis of academic performance and technological engagement. The results indicate that the ASWAJA Smart School model at SMP Khadijah not only enhances students’ understanding of Islamic teachings but also significantly improves their digital skills, preparing them for future challenges in a technology-driven world.In conclusion, the research demonstrates that the integration of ASWAJA values with smart school practices fosters a balanced educational environment that nurtures both spiritual and intellectual growth. The study recommends further development of such programs in other Islamic institutions to equip the next generation with both moral integrity and technological competence.